Elektronski sestavi: Laboratorijske vaje - Donaj, Gregor; Kramberger, Iztok (University of Maribor Press, 2021)
Electronic Systems: Laboratory Excercises. The material contains the instructions for laboratory work in the subject Electronic systems for students of the master’s study programs Electrical Engineering, option electronics, and the master’s study program Telecommunications. The instructions include five laboratory exercises that deal with data converters and the processing, generation, and recognition of digital signals. Exercises include data converters, digital filters, direct digital synthesis, digital phase-locked loops, and digital modulation schemes.